Pengaruh Work-Life Balance, Beban Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai PT. Bank Negara Indonesia (PERSERO) TBK, Kantor Cabang Manado - Poluan, alfian ranny (Universitas Sam Ratulangi, 2018)
The result of this researchs show that work-life balance, workload and leadership style simultaneously have a significant effect on employee performance, this is prove by the F test which shows a significance value 0,006 smaller than 0,05. The result of t test show : 1) work-life balance has a signifianct effect on employee performance with a significance value 0,029 smaller than 0,05. 2) workload has a significant effect on employee performance with a significance value 0,044 smaller than 0,05. 3) leadership style has no significant effect on employee performance with a significance value 0,161 bigger than 0,05. From the test result with the t test also known that the variables that have a dominant effect on employee performance is work-life balance because the significance value is smaller than others variableKeywords: work-life balance,workload, leadership style, employee perfromance